2020
DOI: 10.1101/2020.03.21.001529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In response to Liet al.: Linker histones function inDrosophilaembryogenesis

Abstract: In an earlier paper (Pérez-Montero et al., 2013), we reported that the embryonic linker histone of Drosophila dBigH1 was essential for early Drosophila embryogenesis since embryos homozygous for the bigH1 100 mutation showed strong defects and did not survive beyond zygotic genome activation (ZGA) at cellularization. Recent results challenge these observations since null bigH1 mutations generated by CRISPR/Cas9 methodology turn out to be homozygous viable, as reported in Li et al. (2019) and here. In this rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…To study the specific developmental role of BigH1, we generated transgenic animals that express chimera linker histones constructed by domain switches between somatic H1 and germline/early embryo-specific BigH1. Analysis of the resulting flies revealed that under normal conditions H1 can replace BigH1 effectively and the embryogenesis proceeds without major defects, which confirms the findings of recent studies ( 31 , 32 ). However, sublethal phenotypes, such as nuclear fallout can be observed in mutants where the central globular and C-terminal domains of BigH1 are replaced with those of H1, indicating that these protein regions are necessary for function.…”
Section: Discussionsupporting
confidence: 88%
“…To study the specific developmental role of BigH1, we generated transgenic animals that express chimera linker histones constructed by domain switches between somatic H1 and germline/early embryo-specific BigH1. Analysis of the resulting flies revealed that under normal conditions H1 can replace BigH1 effectively and the embryogenesis proceeds without major defects, which confirms the findings of recent studies ( 31 , 32 ). However, sublethal phenotypes, such as nuclear fallout can be observed in mutants where the central globular and C-terminal domains of BigH1 are replaced with those of H1, indicating that these protein regions are necessary for function.…”
Section: Discussionsupporting
confidence: 88%
“…Though highly speculative, dBigH1 might regulate transcriptional activity in these cells during dumping. Of note, nuclear αdBigH1 immunostaining of germ cells was abolished in a null dBigH1 NSTOP CRISPR/CAS9 mutant [ 43 ], showing its specificity (electronic supplementary material, figure S3). By contrast, background αdBigH1 immunostaining observed in the cytoplasm and somatic FC was also detected in the null dBigH1 NSTOP mutant, indicating it was unspecific (electronic supplementary material, figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that dBigH1 and dH1 preferentially target different genomic loci since ectopic dBigH1 expression in S2 cells has shown that dBigH1 preferentially binds to and displaced dH1 from silent genomic regions with high dH1 content [ 71 ]. On the other hand, recent results suggest a more complex situation since, in null bigH1 mutants generated by CRISPR/CAS9, the lack of maternal dBigH1 is compensated by the expression of somatic dH1 from the earliest stages of embryo development [ 43 , 72 ], suggesting that dBigH1 represses dH1 expression in the early Drosophila embryo. Further work is required to reach a better understanding of the actual link(s) between dBigH1 and dH1 expression and deposition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations